High hydrostatic pressure processing: a method having high success potential in pollen protein extraction - Altuner, Ergi̇n Murat; Ceter, Talip; Alpas, Hami (Informa UK Limited, 2012)
Even a single peptide that is present in the pollen wall and cytoplasm could cause pollen allergy. To produce skin-prick test kits, the first step is the extraction of these molecules. In this study, Cedrus atlantica pollens were subjected to 220 and 330 MPa for 10 and 30 min in order to extract these molecules. After high hydrostatic pressure processing (HHPP), the total amounts of proteins (TAPs) are measured and compared with the results of the conventional extraction method (CEM). As a result, the TAPs extracted by HHPP is 18.0210 μ g/mL at 220 MPa for 10 min, 22.5770 μ g/mL at 220 MPa for 30 min, 23.3810 μ g/mL at 330 MPa for 10 min and 25.9270 μ g/mL at 330 MPa for 30 min, while this is 1.9460 μ g/mL in 24 h by the CEM. In addition to these results, visual pollen deformation and eruption, pollen wall and surface damage have also been observed.
Keywords: High hydrostatic pressure processing; Pollen protein extraction; Cedrus atlantica; Atlas cedar